An Alternative in Managing Duane Retraction Syndrome Type I Using Modified Nishida Procedure: A Case Report: Poster Presentation - Case Report - Resident - Dearaini; Anna Puspitasari Bani (Majalah Oftalmologi Indonesia, 2023)
Introduction : Various surgical approaches have been proposed to address the challenge in managing abduction deficit in Duane Retraction Syndrome (DRS) Type I, with no clear guidelines to achieve optimal result. This report aims to describe the outcome of combining medial rectus (MR) recession and modified Nishida procedure to improve abduction in DRS Type I. Case Illustration : Twenty six year-old female came with inability to abduct her left eye (LE) since early childhood and an abnormal left head turn. No complaints of double vision nor visual impairment. There was -5 abduction on LE with a noticeable narrowing of vertical palpebral fissure during adduction. Prism alternate prism cover test shared a 30 PD esotropia with normal anterior and posterior segment. Patient was assessed with DRS Type I of LE and managed with 5mm MR recession combined with modified Nishida procedure (vertical rectus transposition without tenotomy and muscle splitting). On postoperative day 1 and last follow-up (1 year), the alignment was ortophoric, abduction improvement of -2, and diminished anomalous head posture. Discussion : Although studies have only reported successful cases of modified Nishida procedure in CN VI palsy, it can be assumed that the procedure can also be implemented to treat lateral rectus muscle innervation abnormality such as in DRS type I. Surgical intervention may not normalize abduction deficit. However, the procedure successfully corrects ocular alignment, eliminates anomalous head posture, and able to improve abduction with no complications. Conclusion : Modified Nishida procedure can be implemented as an alternative in managing DRS type I with relatively satisfactory result.